Inflammatory stimuli and hypoxia on atherosclerotic plaque thrombogenicity: Linking macrophage tissue factor and glycolysis - Kazunari Maekawa; Eriko Nakamura; Yoichi Saito; Yunosuke Matsuura; Toshihiro Gi; Kensaku Nishihira; Nobuyuki Oguri; Sayaka Moriguchi-Goto; Yuichiro Sato; Kinta Hatakeyama; Yoshisato Shibata; Yoshihiro Komohara; et al. (PLoS ONE, 2025)
Background The thrombogenic potential of cells within atherosclerotic plaques is critical in the formation of a coronary thrombus. We hypothesized that a combination of inflammatory and hypoxic stimuli enhances tissue factor (TF) expression and glycolysis in cells in atherosclerotic plaques and contributes to coronary thrombus formation. Aims To identify TF- and hexokinase (HK)-II-expressing cells in coronary atherosclerotic plaques and thrombi and determine the effects of combined inflammatory and hypoxic stimuli and glycolysis on TF expression in peripheral blood mononuclear cell-derived macrophages. Methods We immunohistochemically assessed TF and HK-II expression in stable (n =  20) and unstable (n =  24) human coronary plaques and aspirated acute coronary thrombi (n =  15). The macrophages were stimulated with tumor necrosis factor-α, interferon-γ, or interleukin-10 under normoxic (21% O2) or hypoxic (1% O2) conditions, and TF expression was assessed. Results TF and HK-II expression were increased in unstable plaques compared with stable plaques. The number of CD68- and HK-II-immunopositive cells positively correlated with the number of TF-immunopositive cells. TF- and HK-II-expressing macrophages, which expressed M1- or M2-like markers, were involved in platelet-fibrin thrombus formation in ruptured plaques. The combination of inflammatory and hypoxic conditions additively augmented TF expression and procoagulant activity in the cultured macrophages. Inhibition of glycolysis with 2-deoxyglucose reduced the augmented TF expression and procoagulant activity. Conclusion Combined inflammatory and hypoxic conditions in atherosclerotic plaques may markedly enhance procoagulant activity in macrophages and contribute to coronary thrombus formation following plaque disruption. Macrophage TF expression may be associated with glycolysis.